Development of the General Practitioner Competency Model Using Grounded Theory for Assessing General Practitioners' Competencies in Delivering Contracted Care Services - MA Zhiqiang, GUO Le, LI Zhao, GE Bailin (Zhongguo quanke yixue, 2023)
Background There is an issue of mismatch between supply and demand of medical care resources in China. The implementation of contracted family doctor services is an effective measure to address the issue, and to improve the hierarchical diagnosis and treatment system. Therefore, it is urgent to speed up the training and ensure the training quality of general practice workforce. Objective To develop a comprehensive and systematic general practitioner (GP) competency model after analyzing the concept and structural domains of competencies (including inner competencies) required for GPs to deliver contracted healthcare services, providing insights into the realization of training eligible GPs in terms of quantity and quality, and the improvement of quality and efficiency of contracted services. Methods From December 2020 to September 2021, we conducted in-depth, semi-structured interviews with 38 GPs from 10 medical institutions in four cities (Zhenjiang, Taizhou and Suzhou in Jiangsu Province, and Foshan in Guangdong Province) , then treated the interview results applying the three-level coding and theoretical saturation used in the grounded theory. After that, we developed a General Practitioner Competency Model. Results The model consists of 10 items, which belong to four domains: general care capability, humanistic practice capability, team cooperation capability, learning and development capability. General care capability and learning and development capability belong to external competencies, which represent the external performance and driving force of competencies, and determine the level of competencies of GPs to provide contracted services. Humanistic practice capability and team cooperation capability reflect the internal traits and competencies, which belong to the inner competencies, and determine the potential of GPs to provide contracted services. Conclusion The model developed by us is complete and comprehensive, in which the inner competencies of GPs have been fully explored, which may be contributive to the training of GPs delivering contracted services, and to the development of a GP competency assessment system using quantitative empirical methods.